Shear Stress-Induced Changes in Platelet Reactivity - Yu, Simmon K; Latour, Jean-Gilles; Marchandise, Baudouin; Bois, Marc (Thrombosis and Haemostasis, 1978)
We have investigated the effects on platelet function of a physiologic shear stress. The aggregation to thrombin and collagen, the release reaction [(14C) serotonin] and the procoagulant activity of washed platelet suspensions were assayed on samples undergoing laminar oscillatory flow for 20 minutes at 37° C in polyethylene tubes, and on paired samples kept at rest. The pulse rate was established at 72 cycles per minute and the shear stress at the wall estimated at 26.2 dynes/cm2. The platelet suspensions were prepared at 37°C from blood samples of 15 healthy volunteers and 15 patients with the diagnosis of coronary artery disease proven by angiography. Our results show enhancement of platelet aggregation in samples undergoing oscillatory flow. Furthermore, platelets from coronary patients gained additional procoagulant activity. However, no change was encountered in the rate and speed of the release reaction. It is concluded that exposure to a high shear stress within an oscillatory flow system enhances platelet reactivity; this reaction may take part in the production of platelet and coagulation changes seen in the atherosclerotic patient and after strenuous physical exercise.